STRATEGI PEMBELAJARAN MEMBACA AL QURAN DENGAN METODE SOROGAN PADA SISWA KELAS 6 SD NEGERI 2 GONDANG, KECAMATAN PURWANTORO, KABUPATEN WONOGIRI - Yunus, Muhammad; Parwiyanti, Septia (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2025)
The purpose of this study was to improve students' ability to read the Quran. The sorogan method is a teaching method in which students are emphasized to be more active in facing the teacher one by one in turns by reading a book or scripture that has been determined. The method used in this study is a qualitative approach with a descriptive research type. Data collection techniques used observation, interview, and documentation techniques. The results of the study showed that students' ability to read the Quran increased significantly. Of the 16 6th grade students: (a) 6 students (37.5%) who were initially not fluent became quite fluent in 4 months of implementing the method. (b) 8 students (50%) experienced improvements in the aspects of tajwid and makhraj. (c) 2 students (12.5%) were able to read with tartil and became references for their friends.